PERMAINAN BOWLING TERHADAP KEMAMPUAN MOTORIK KASAR ANAK AUTIS - Julistia Harista, Nita (Jurnal Pendidikan Khusus, 2016)
ABSTRACT A part of autism children had obstacle in gross motoric, therefore, to solve the problem was needed the activity attracting the children, one of the activities used to attract the children was bowling game. Bowling game was the game which mostly used the strength of hands muscles. The purpose of this research was to prove the influence of bowling game toward gross motoric ability to autism children in TK Mentari School Sidoarjo. The research method used quantitative approach the data was collected using a test of participant’s gross motoric ability and documentation, the test of participant’s gross motoric ability was used to obtain the data of gross motoric ability to autism children before and after giving treatments while the data from documentation was used as the support data or proof that the research was really done. The research result indicated that in initial observation / pre test, the average obtained was 47,9 and after giving treatment in the final observation / post test the average obtained was 77,08. It indicated that there was significant enhancement. Zh value = 2,20 was greater than critic value 5% Zt = +1,96 which meant that Ho was refused and Ha was accepted so it could be stated there was influence of bowling game toward gross motoric ability to autism children in TK Mentari School Sidoarjo.   Keywords: bowling game, gross motoric